Transhumant Mobility And Customary Resource Regulation In The Imghrane Communauty (Southeast Morocco) - Mohamed El Mouaaine (International Journal of Scientific Research and Innovative Studies, 2025)
Transhumance is one of the main forms of mobility in Amazigh societies, where it plays a central role in economic, social, and territorial organization.. In the Imghrane region, this ancestral practice relies on the careful management of agro-pastoral resources and seasonal movements that ensure complementarity between mountain areas and oases. Herd mobility is regulated by local institutions and customary knowledge passed down thru generations, allowing for continuous adaptation to climatic and environmental constraints. At the heart of this system, the Agdal emerges as a key institution, with ecological, social, and symbolic dimensions, ensuring both the preservation of pastures and fairness in access to resources. However, recent transformations—sedentarization, demographic pressures, rural exodus, and market integration—are undermining these balances and raising questions about the future of pastoral mobility. This article aims to analyze the forms of mobility in transhumance in the Imghrane oasis, highlighting traditional mechanisms of space management, the multiple roles of the Agdal, and the contemporary challenges of sustaining pastoral practices. Keywords: Amazigh, Imghrane, Transhumance, Spatial mobility, Agro-pastoralism, Agdal. Received Date: July 19, 2025 Accepted Date: August 11, 2025 Published Date: August 30, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/436